The Effectiveness of the Use of Ordinary Hops in the Production of Fermented Milk Products - S. T. Kyrykbaeva; Z. Kalibekkyzy; S. K. Zhakupbekova; A. K. Beisembayeva; B. M. Silybayeva (Алматы технологиялық университетінің хабаршысы, 2022)
The article tells about ordinary hops growing in the East Kazakhstan region, which can currently be used as raw materials for the production of environmentally friendly and cost-effective food products, collecting natural plant products to increase the competitiveness of their products in a market economy. The ordinary hops taken for research were collected from special Semey forestry and dried in a special dry room. The study showed that ordinary hops contain vitamins A, D3 C, B-carotene and amino acids, saponins, alkaloids, silt substances. Also, the composition of ordinary hops is rich in macro-microelements. Among these elements there is a very high content of Ca, K, Fe, Mg, which are necessary for the human body. In connection with these results, an extract of the hop plant was obtained. In addition, the hop plant can be used not only in brewing in the production of bread, but also in the production of dairy products.